SOCS3 Suppression Promoted the Recruitment of CD11b+Gr-1−F4/80−MHCII− Early-Stage Myeloid-Derived Suppressor Cells and Accelerated Interleukin-6-Related Tumor Invasion via Affecting Myeloid Differentiation in Breast Cancer - Zhang, Wenwen; Jiang, Mengmeng; Chen, Jieying; Zhang, Rui; Ye, Yingnan; Liu, Pengpeng; Yu, Wenwen; Yu, Jinpu (Frontiers in Immunology, 2018)
Interleukin-6 (IL-6) is an important trigger for the expansion and recruitment of myeloid-derived suppressor cells (MDSCs), which are regarded to be major coordinators of the immunosuppressive tumor microenvironment. In this study, we constructed IL-6-knockdown breast cancer mice models to explore the molecular events involved in the IL-6-mediated effects on MDSC development. We defined a subset of early-stage MDSCs (e-MDSCs) with the phenotype of CD11b+Gr-1−F4/80−MHCII− in IL-6 high-expressing 4T1 mice mammary carcinoma models, which were the precursors of CD11b+Gr-1+ conventional MDSCs. Furthermore, sustained suppression of SOCS3 and aberrant hyperactivation of the JAK/STAT signaling pathway was exclusively detected in wide-type 4T1 tumor-bearing mice, which promoted the accumulation of e-MDSCs in situ and their immunosuppressive capability in vitro. After blocking the IL-6/STAT3 signaling pathway with the IL-6 receptor antibody or STAT3 antagonist JSI-124 in tumor-bearing mice, significant shrinkage of primary tumors and decrease in lung metastatic nodules were observed in vivo, accompanied by the dramatic decrease of e-MDSC recruitment and recovery of anti-tumor T cell immunity. Thus, SOCS3 suppression accelerated the IL-6-mediated growth and metastasis of mammary carcinoma via affecting myeloid differentiation in breast cancer. Moreover, the IL-6/STAT3 signaling pathway might be a promising candidate target in developing novel therapeutic strategies to eliminate e-MDSCs and improve breast cancer prognosis.